An Epidemiological Model with Multiple Endemic States - Villavicencio Pulido, José Geiser; Barradas Bribiesca, José Ignacio; Luna Olivera, Beatriz Carely (Journal of Biological Systems, 2015)
We present a model describing the dynamics of an infectious disease for which the force of infection is diminished through a reaction of the susceptible to the number of infected individuals. We show that, even though the structure of the model is a simple one, different kinds of backward bifurcation can appear for values of the basic reproductive number bigger than one. Under some conditions on the parameters, multiple endemic equilibria may appear for values of the basic reproductive number less or greater than one.
Keywords: Estado endémico múltiple; Modelo epidemiológico; Bifurcación inversa